The Development of Mixed-Media Art Creation Process from Waste Materials to Improve Communication Efficiency - Thongprong, Arkom; Promrat, Thaveerat (Journal of Ecohumanism, 2025)
Purpose: The present economic and technological growth has increased goods manufacturing rapidly and led to the problem of waste material management. This research aims to study the cause of the problem, its impact, and solutions to reduce the pollution resulting from the increasing amount of waste. It explores various forms of art and concepts from Dadaism till the present, which used waste materials in artistic expression, developing the concept of mixed-media art from waste materials to create perception and feedback from the audience in the most effective way both aesthetically and in making the awareness among the public about the utilization and management of the waste materials that are creating problems to our lives and environment. Method: This is a research and development study. Using Roland Barthes’ semiology theory, the research experiments and explores the art creation process using waste materials to create mixed-media art within the frameworks of two-way or feedback methods. Develop ways of communication and experiment with waste materials to make the artworks that can communicate and invite feedback from the audience, display the artworks in public space, and document the interactions from the audience for further improvement of the artworks Result: This research's evaluation results have a very good total average (x̅ = 4.60, S.D. = 0.56) for form achievement and an excellent total average (x̅ = 4.52, S.D. = 0.57) for conceptualization achievement of creative development from waste materials. Conclusion: Using waste materials as a means of artistic expression is also a good way to give new values to the so-called ‘waste’ and open up possibilities and meanings from the audience’s point of view. In turn, this may help reduce the accumulation of waste, a challenge our society is confronting.